Kedudukan Notaris dan PPAT dalam Perjanjian Jual Beli Tanah dan Jaminan Perlindungan bagi Para Pihak - I Komang Edy Susanto; Ida Ayu Putu Widiati; Ni Gusti Ketut Sri Astiti (Warmadewa Press, 2020)
Basically, notaries also serve as Land Deed Making Official (hereafter called PPAT) after they carry out a test. Thus, in carrying out their role as PPAT, they are entitled to make deeds of transferring land rights. Based on this background, this research was conducted with the aim of describing how the position of the notary and PPAT in transferring land rights and how legal protection for parties who transfer land through sale and purchase. The research method used in this research was a normative legal method. The results of this study indicated that the position of a notary in the transfer of land rights as an official deed maker is mentioned in article 2 paragraph (1) of Law No. 2/2014 concerning the Position of Notary, which states that a notary is a public official who is authorized to make authentic deeds and has other powers as referred to in this Law or based on other Prevailing Laws. The position of the PPAT in essence has the task of carrying out land registration by making deeds as evidence and having carried out certain legal actions regarding land rights. Legal protection for parties transferring land through sale and purchase is stated in the 1945 Constitution, namely Article 27 paragraph (1) which states that each person has the right to recognition, guarantee, protection, and legal certainty that is just and equal treatment before the law.